2018
DOI: 10.1016/j.jvb.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination trajectories during police officers' vocational training program: A growth mixture analysis

Abstract: Self-determination trajectories during police officers' vocational training program: A growth mixture analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 120 publications
5
26
0
Order By: Relevance
“…Since the purpose is the basis of the model and determines the content of all pedagogical components (Gillet et al, 2018), the first and most significant element of the model for supporting professional self- 502 support for professional self-determination for students of technical universities is to develop the competence of professional self-determination of subjects of pedagogical support (applicants, students, masters, graduate students) (Beebe & Masteerson, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Since the purpose is the basis of the model and determines the content of all pedagogical components (Gillet et al, 2018), the first and most significant element of the model for supporting professional self- 502 support for professional self-determination for students of technical universities is to develop the competence of professional self-determination of subjects of pedagogical support (applicants, students, masters, graduate students) (Beebe & Masteerson, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, these studies reveal slightly decreasing trajectories of autonomous motivation and slightly increasing trajectories of controlled motivation as students become older (e.g., Leroy & Bressoux, 2016;Maulana et al, 2013). One more recent study (Gillet et al, 2018a) of upcoming police officers undergoing vocational training revealed that three profiles best represented trainees' motivational trajectories over a period of 41 weeks: (a) one displaying high initial levels of autonomous motivation and a slight increasing tendency; (b) one displaying moderate initial levels of autonomous motivation and a very slight decreasing tendency; and (c) one displaying low initial levels of autonomous motivation and a slight decreasing tendency.…”
Section: Empirical Evidencementioning
confidence: 94%
“…A second intimately-related limitation stems from the dearth of research evidence concerning the characteristics of the training context involved in supporting autonomous motivation and limiting controlled motivation. In this regard, Gillet et al (2018a) did document the role of demands and resources linked to the training context (peer support, work load, emotional load, and mental load; similar work characteristics were also studied by Fernet et al, 2020a). However, it would be even more informative for purposes of intervention to focus on drivers falling more directly under the control of the trainers, such as their autonomy-supportive behaviors (Deci et al, 1989), which are a focal point of the present study.…”
Section: Empirical Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…In employee motivation realms, workers view stressors (in our case, negative feedback information) as challenges or hindrances to goal achievement. These beliefs, then, become the basis for future effort and demand expectations (Gillet et al, 2018). According to Cavanaugh, Boswell, Roehling, and Boudreau (2000), motivation and ability to adjust to goal-attainment threats are dependent on the appraisal.…”
Section: A Goal-setting Framework Of Gritmentioning
confidence: 99%